Statistical Method for Testing of Sigma-Delta Converters - J. Vedral; J. Holub (Acta Polytechnica, 2000)
Measurement and testing methodology for 2-channel insulated measuring module based S - D on Analog-to-Digital converter AD7710 that has a nominal resolution 16(24) bits is presented. The dependencies of effective resolution on the first notch frequency and gain are given.